PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS XII IPA SMA N 7 PADANG - Putri Pramyta Agusti (Jurnal Edukasi dan Penelitian Matematika, 2019)
Mathematical communication is one of abilities that students should have it in mathematics learning. However, the fact showed that students’ communication ability of XII IPA SMAN 7 Padang were low. Based on observation, it could be concluded that the learning was teacher - centered which caused students learned passively. One of solutions that could be done was applying  cooperative learning model of  TSTS type. This research was both descriptive and quasi experiment with randomized control group pretest - posttest design. Based on analysis, it got that P-value = 0,010, so it can be concluded that students’ who study with TSTS learning model is better than students’ who study with conventional learning. Therefore, students’ mathematical communication ability who study with cooperative learning of TSTS type is better than students’ who study with conventional learning.Keywords– conventional learning, cooperatif learning type TSTS, mathematical communication abilities.